Importance and Relevance of Focusing and Improving Sidewalk Design (Eurasian Journal of Engineering and Technology, 2022)
The article cites a number of factors that make walking paths and walks an important part of social life and that properly organized walking paths are an important factor in improving the country's ecology, public health and maintaining a balanced lifestyle. It draws on the experience and findings of developed countries, the latest data from the World Health Organization and air quality in Europe. It has been studied that the design of roads in the urban planning of developed countries is oriented towards the interests and convenience of pedestrians, and many results have been achieved in this regard